2020
DOI: 10.1016/j.acap.2020.05.008
|View full text |Cite
|
Sign up to set email alerts
|

School-Based Telemedicine Interventions for Asthma: A Systematic Review

Abstract: BACKGROUND: School health systems are increasingly investing in telemedicine platforms to address acute and chronic illnesses. Asthma, the most common chronic illness in childhood, is of particular interest given its high burden on school absenteeism. OBJECTIVE: Conduct a systematic review evaluating impact of school-based telemedicine programs on improving asthmarelated outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
(61 reference statements)
0
13
0
Order By: Relevance
“…The impact of telemedicine on asthma‐related clinical outcomes, such as symptoms, pulmonary function, healthcare utilization and medication use, was also investigated, as well as patient/parent satisfaction and QoL (Figure 1). 64,65 As reported by recent systematic reviews, the available evidence supporting the introduction of telemedicine for asthma management showed conflicting data, but none of the included studies indicated adverse effects 64,65 …”
Section: The Potential Role Of Telemedicine In the Management Of Paediatric Asthmamentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of telemedicine on asthma‐related clinical outcomes, such as symptoms, pulmonary function, healthcare utilization and medication use, was also investigated, as well as patient/parent satisfaction and QoL (Figure 1). 64,65 As reported by recent systematic reviews, the available evidence supporting the introduction of telemedicine for asthma management showed conflicting data, but none of the included studies indicated adverse effects 64,65 …”
Section: The Potential Role Of Telemedicine In the Management Of Paediatric Asthmamentioning
confidence: 99%
“…Telemedicine QoL (Figure 1). 64,65 As reported by recent systematic reviews, the available evidence supporting the introduction of telemedicine for asthma management showed conflicting data, but none of the included studies indicated adverse effects. 64,65 In the context of the rapid worldwide spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), telemedicine might provide an additional and essential resource for managing children with asthma, replacing in-person visits.…”
Section: The P Otential Role Of Telemed I Cine In the Manag Ement Omentioning
confidence: 99%
See 1 more Smart Citation
“…Maximizing the use of available asthma medications before considering the moreexpensive alternatives (including improved methods to enhance adherence to conventional therapy) [67][68][69] and ensuring access to mobile technology for the implementation of telemedicine in homes, clinics, and schools would help. 68,[70][71][72] Telemedicine will be particularly beneficial in rural, underserved communities because 94% of the population has broadband access, but ensuring reliable access to racial and ethnic minority groups in rural areas will be necessary. In urban settings, because indoor allergen and pollutant triggers in the built environment can exacerbate asthma, home visits can be an important adjunct to the medical evaluation.…”
Section: What Needs To Be Done?mentioning
confidence: 99%
“…In urban settings, because indoor allergen and pollutant triggers in the built environment can exacerbate asthma, home visits can be an important adjunct to the medical evaluation. 39,[69][70][71][72] In academic, private, and institutional health system settings, cross-cultural education to reduce provider bias is crucial. 6 More inverventional studies such as the BRief Evaluation of Asthma Therapy study will be instrumental in the future to help inform efforts to correct asthma disparities and inequities.…”
Section: What Needs To Be Done?mentioning
confidence: 99%